2007
DOI: 10.1007/s00125-007-0822-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of retinal vascular calibre to diabetes and retinopathy: the Australian Diabetes, Obesity and Lifestyle (AusDiab) study

Abstract: Aims/hypothesis The aim of the study was to examine the relationship of retinal vascular calibre with glucose intolerance, diabetes and retinopathy in a population-based cohort. Methods The Australian Diabetes, Obesity and Lifestyle study recruited adults aged ≥25 years old from across Australia. Participants were classified using an oral glucose tolerance test as having normal glucose tolerance (NGT), impaired glucose tolerance (IGT), impaired fasting glucose (IFG), known diabetes or newly diagnosed diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 34 publications
5
53
3
Order By: Relevance
“…20 Our study now clearly shows that in Asian Malays, as in white population, wider retinal arterioles are associated with diabetes. The association of wider retinal venules with diabetic retinopathy signs in our study is also consistent with clinical experience, as well as with findings from white population from BMES, 10 AusDiab, 8 MESA, 7 and Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR). 6,9 The mechanisms underlying wider retinal arterioles with diabetes are uncertain, but multiple aetiologies have been suggested, including impaired autoreguation of small vessels caused by hyperglycaemia and hypoxia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…20 Our study now clearly shows that in Asian Malays, as in white population, wider retinal arterioles are associated with diabetes. The association of wider retinal venules with diabetic retinopathy signs in our study is also consistent with clinical experience, as well as with findings from white population from BMES, 10 AusDiab, 8 MESA, 7 and Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR). 6,9 The mechanisms underlying wider retinal arterioles with diabetes are uncertain, but multiple aetiologies have been suggested, including impaired autoreguation of small vessels caused by hyperglycaemia and hypoxia.…”
Section: Discussionsupporting
confidence: 91%
“…8 Data from MESA study suggest that there may be racial variation of the effect of diabetes on the retinal vascular calibre. However, due to the small number of Asian participants, such an observation would need confirmation by other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonmydriatic digital retinal photographs were taken at baseline (14). Retinal vascular caliber was measured using a validated computer-based program by trained graders masked to participant characteristics (16). If retinal vascular caliber could not be measured from photographs of the right eye, the left was used.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that alterations in the retinal architecture, as reflected by variations in retinal vascular calibre, may be a marker of prediabetes, diabetes and its microvascular complications [1][2][3] measurements, however, offer information on a single specific variable of the retinal vascular network.…”
Section: Introductionmentioning
confidence: 99%